2006
DOI: 10.1002/ps.1197
|View full text |Cite
|
Sign up to set email alerts
|

Rapid bidirectional allele‐specific PCR identification for triazine resistance in higher plants

Abstract: Triazine resistance is reported to be due to chloroplast herbicide target insensitivity in most species, and this is most often caused by a Ser(264)-Gly mutation at the D1 protein. In order to ascertain whether this mutation is really predominant amongst resistant plants, and also for gene flow studies, a rapid test is needed that allows the testing of large quantities of plants. Here a bidirectional allele-specific PCR (polymerase chain reaction) identification is proposed. The designed primers were shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…These results confirm the results of Tian and Darmency (2006), Park and MallorySmith (2006) and Elahifard et al (2013a), with a slight difference from Elahifard et al (2013a) in S-biotype sequencing. They reported a serine-to-glycine substitution in codon 282 in addition to the 232 position but the results of the present study found no such substitution at the 282 site for the S and R biotypes.…”
Section: Comparing Paba Gene Sequence In S and R-biotypessupporting
confidence: 90%
“…These results confirm the results of Tian and Darmency (2006), Park and MallorySmith (2006) and Elahifard et al (2013a), with a slight difference from Elahifard et al (2013a) in S-biotype sequencing. They reported a serine-to-glycine substitution in codon 282 in addition to the 232 position but the results of the present study found no such substitution at the 282 site for the S and R biotypes.…”
Section: Comparing Paba Gene Sequence In S and R-biotypessupporting
confidence: 90%
“…Populations of many other weed species also exhibited the same resistance . In most cases, triazine resistance was due to a point mutation (Ser‐264‐Gly) on the chloroplast gene psbA ; psbA encodes for the thylakoid D1 protein, which is critical for photosystem II energy transfer . This mutation results in a conformational change of the D1 protein, though the protein continues to function, otherwise, the electron transfer would be blocked.…”
Section: Triazine Resistancementioning
confidence: 99%
“…Tian and Darmency (2006) identified a point mutation related to triazine resistance in higher plants, which caused a Ser 264 -Gly substitution that confered resistance in Setaria italica. Park and Mallory-Smith (2006) analyzed the nucleotidic sequence in one bromoxynil-resistant S. vulgaris biotype and identified a point mutation which induced the amino acid substitution from asparagine to threonine at codon 266.…”
Section: Analysis Of the Sequenced Ampliconsmentioning
confidence: 99%